On the Move to Meaningful Internet Systems: OTM 2010 Workshops Confederated International Workshops and Posters: International Workshops: AVYTAT, ADI, DATAVIEW, EI2N, ISDE, MONET, OnToContent, ORM, P2P-CDVE, SeDeS, SWWS and OTMA. Hersonissos, Crete, Greece, October 25-29, 2010. Proceedings - Meersman, Robert; Dillon, Tharam; Herrero, Pilar; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
This volume constitutes the refereed proceedings of 11 international workshops held as part of OTM 2010 in Hersonissos, Greece in October 2010. The 68 revised full papers presented were carefully reviewed and selected from a total of 127 submissions to the workshops. The volume starts with 14 poster papers of the OTM 2010 main conferences COOPIS 2010, DOA 2010 and OSBASE 2010. Topics of the workshop papers are adaption in service-oriented architectures, ambient intelligence and reasoning, data integration approaches, modeling in ADI, web and enterprise data visualization, enterprise integration and semantics, industrial enterprise interoperability and networking, process management in distributed information system development, improving social networking, ontology engineering, master data management and metamodeling, extensions to fact-oriented modeling, logic and derivation, patterns in input data models.
On the Move 2010 Keynotes -- Posters and Industry Papers of the COOPIS 2010 International Conference -- Posters of the DOA 2010 International Conference -- Posters of the ODBASE 2010 International Conference -- Workshop on Adaptation in serVice EcosYsTems and ArchiTectures (AVYTAT 2010) -- Adaptation in Service-Oriented Architectures -- Workshop on Ambient Data Integration (ADI 2010) -- Ambient Intelligence and Reasoning -- Data Integration Approaches -- Modeling in ADI -- Workshop on DATA Visualization and Integration in Enterprises and on the Web (DATAVIEW 2010) -- Web and Enterprise Data Visualization -- Semantic Web Data Integration and Visualization -- Workshop on Enterprise Integration, Interoperability and Networking (EI2N 2010) -- EI2N Keynote Paper -- Enterprise Integration and Semantics -- Industrial Enterprise Interoperability and Networking -- Workshop on Information Systems in Distributed Environment (ISDE 2010) -- Process Management in Distributed Information System Development -- Distributed Information Systems: Implementation Issues -- Workshop on MObile and NEtworking Technologies for social applications (MONET 2010) -- Improving Social Networking: Service-Oriented Architectures, Location-Based Services, and Multimodality -- Adaptive Issues and Solutions in Networking and Mobile Applications -- Workshop on Ontology Content (OnToContent 2010) -- Ontology Engineering -- Ontology in Social Entreprise -- Workshop on Fact-Oriented Modeling (ORM 2010) -- Data Integration -- Master Data Management and Metamodeling -- Extensions to Fact-Oriented Modeling -- Logic and Derivation -- Patterns in Input Data and Data Models -- Workshop on P2P Collaborative Distributed Virtual Environments (P2P CDVE 2010) -- Workshop on Semantic and Decision Support (SeDeS 2010) -- Workshop IFIP on Semantic Web and Web Semantics (SWWS 2010) -- On The Move Academy (OTMA 2010) -- Position Papers -- Technical Papers.
Keywords: Computer science; Computer Communication Networks; Software engineering; Information storage and retrieval systems; Information systems; Artificial intelligence; Computer Science; Computer Communication Networks; Information Systems Applications (incl.Internet).; Software Engineering; Information Storage and Retrieval; Artificial Intelligence (incl. Robotics).; Programming Techniques